A condução argumentativa promovida por articuladores na produção textual de alunos do Ensino Fundamental - Schneider, Glaci Terezinha (2013)
This research is a deployment of the project Theoretic reflection and application in classroom: linguistic analysis as a support in text production of a Parana state public school, developed in partnership with Fundação Araucária in 2011. The project s goal was to develop in the 9th year students of the basics education the argumentative writing production, and had as a theoretic contribution the studies of the Argumentative Semantics and Textual Linguistics, supporting theoretic basis present also in the analysis showed in this paper. Our participation in the research enabled checking at the surveyed students writing how the argumentative development occurred, especially in the coordinative conjunctions were triggered in the writing and rewriting process and how the students react in face of the developed activities. After the student s material production analysis, we selected as corpus of this research, the texts produced by two students, the subjects of this research, one text in the redação escolar genre, produced before the project s intervention, and, the last version of the scientific article genre, produced during the research activities. The performed analysis allowed verify that there is an argumentative enunciation directed by coordinative process in the surveyed written production, and that there was a significant use of these elements after the pedagogical activities developed by the application of the project. Also, we perceived the subordination elements linked to the argumentative process. We noticed that the scientific article genre was assimilated in its more general aspects, what show good acceptance by students about the text that reminds scientific research